2017
DOI: 10.1016/j.hpb.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of available evidence in the management of gallbladder and bile duct stones: a systematic review of international guidelines

Abstract: Only five guidelines on gallstones are evidence-based and of a high quality, but even in these controversy exists on important topics. High quality evidence is needed in specific areas before an international guideline can be developed and endorsed worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 40 publications
0
32
0
1
Order By: Relevance
“…The presence of gallbladder polyps causes a clinical problem, since surgery is only absolutely indicated for neoplastic polyps, including adenomas in view of their assumed malignant potential [ 10 13 ]. While international guidelines have various recommendations for the indication of cholecystectomy in general [ 14 ], it is of interest that American [ 15 ] and other western countries [ 16 – 18 ] advocate cholecystectomy for polyps ≥ 1 cm. For polyps < 1 cm, cholecystectomy is only suggested in patients with additional risk factors for malignancy (e.g., older age or primary sclerosing cholangitis (PSC)) or in case of biliary symptoms without alternative causes [ 16 , 17 ].…”
mentioning
confidence: 99%
“…The presence of gallbladder polyps causes a clinical problem, since surgery is only absolutely indicated for neoplastic polyps, including adenomas in view of their assumed malignant potential [ 10 13 ]. While international guidelines have various recommendations for the indication of cholecystectomy in general [ 14 ], it is of interest that American [ 15 ] and other western countries [ 16 – 18 ] advocate cholecystectomy for polyps ≥ 1 cm. For polyps < 1 cm, cholecystectomy is only suggested in patients with additional risk factors for malignancy (e.g., older age or primary sclerosing cholangitis (PSC)) or in case of biliary symptoms without alternative causes [ 16 , 17 ].…”
mentioning
confidence: 99%
“…There are many and different possible treatments that require several skills and specific indication according to the clinical history. Lack of a worldwide consensus on this clinical scenario may be the biggest impediment to establishing guidelines for managing this condition but, when it is possible, the one-stage approach is preferable [21, 22]. We have demonstrated that it is possible to address patients pre-operatively to direct them towards a specific treatment in order to obtain better technical and organizational management of the surgery and a more personalized approach to the patient’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…1 , 2 Since its introduction, the length of stay (LOS) associated with LC has steadily reduced and it is now widely accepted as an appropriate and safe ambulatory procedure in carefully selected patients. 2 , 3 , 4 , 5 Implementation of standard clinical pathways for LC have been reported to successfully reduce LOS and increase day case success. 6 , 7 , 8 , 9 , 10 , 11 , 12 Day case laparoscopic cholecystectomy (DCLC) is associated with cost-savings 3 , 13 , 14 without increasing the risk of adverse events or readmissions.…”
Section: Introductionmentioning
confidence: 99%